2015
DOI: 10.1080/07347332.2015.1045679
|View full text |Cite
|
Sign up to set email alerts
|

Financial Quality of Life for Patients With Cancer: An Exploratory Study

Abstract: For people who are experiencing financial hardship, a cancer diagnosis can be devastating. For others, cancer may exacerbate financial stress, thereby influencing their livelihood, their ability to maintain employment benefits including health insurance, manage financial obligations, and participate meaningfully in cancer treatment. This study examined how vulnerabilities in psychosocial situations affect financial quality of life within the larger context of health-care decision making through a survey conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…Our study population was mostly female (61%), with a mean age older than 50 years, ndings that are consistent with those in other studies involving patients with cancer [6, [12][13][14][15][16][17][18][19]. There was greater participation by individuals who reported being white (60%), although the majority of the Brazilian population self-reports as black [20].…”
Section: Discussionsupporting
confidence: 87%
“…Our study population was mostly female (61%), with a mean age older than 50 years, ndings that are consistent with those in other studies involving patients with cancer [6, [12][13][14][15][16][17][18][19]. There was greater participation by individuals who reported being white (60%), although the majority of the Brazilian population self-reports as black [20].…”
Section: Discussionsupporting
confidence: 87%
“…It is estimated that by 2020, the costs will increase by about EUR 1.5 billion per year in Finland (Ministry of Social Affairs and Health, ). In addition to this, it is difficult to estimate the costs of a decreased quality of life and its consequences (Callahan & Brintzenhofeszoc, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many people do not know what financial benefits they are entitled to, even though some of them have difficulties in paying for food and medicine. According to our participants, patients should receive better guidance on financial support, for example, from social workers-a conclusion that has also been drawn in research into other long-term illnesses (Aaltonen, 2017;Cahallan & Brintzenho-Feszoc, 2015). As a solution, participants suggested that healthcare professionals adopt a more holistic view of patients (Evertsen & Wolkenstein, 2010) and refer them more often to special professionals.…”
Section: A Key Message From the Csf: Placing The Needs Of Cancer Patients And Their Close Ones At The Centrementioning
confidence: 85%